Perancangan E-Learning Berbasis Blended Learning dalam Pembelajaran Fluida Statis - Silva Nurahmih; Dewi Muliyati; Permana, Handjoko (Mitra Pilar: Jurnal Pendidikan, Inovasi, dan Terapan Teknologi, 2024)
Abstract The integration of e-learning in the educational sector plays a pivotal role in enhancing learning effectiveness, particularly in the subject of static fluids. This study aims to create a blended learning-based e-learning design to help students better understand static fluid concepts. The research utilizes a research and development approach following the ADDIE model (analyze, design, development, implementation, and evaluation) and incorporates Moodle's activity analytics feature to monitor student engagement and learning progress. The developed design includes key elements such as interactive learning materials, collaborative activities through discussion forums, quizzes for assessment, and the use of activity analytics to track progress. This approach is expected to support the development of more adaptive features to accommodate students' individual learning needs. Abstrak Integrasi e-learning dalam dunia pendidikan memiliki peran penting dalam meningkatkan efektivitas pembelajaran, terutama pada materi fluida statis. Penelitian ini bertujuan untuk merancang e-learning berbasis blended learning guna meningkatkan pemahaman siswa terhadap konsep fluida statis. Metode yang digunakan adalah pendekatan penelitian dan pengembangan berbasis model ADDIE (analyze, design, development, implementation, dan evaluation) dengan memanfaatkan fitur activity analytics bawaan Moodle untuk memantau aktivitas dan kemajuan belajar siswa. Desain yang dikembangkan mencakup komponen utama seperti materi pembelajaran interaktif, aktivitas kolaboratif melalui forum diskusi, kuis untuk evaluasi, serta pemanfaatan fitur activity analytics dalam memantau progres belajar. Pendekatan ini diharapkan dapat mendorong pengembangan fitur yang lebih adaptif untuk memenuhi kebutuhan belajar individu siswa.